Program Evaluation Certification of Indonesian Library Competence - Opong Sumiati; Muchlis R. Luddin; Ma'ruf Akbar (IJHCM (International Journal of Human Capital Management), 2020)
Librarian Work Competency Certification Program has been implemented since 2013. The significance and sustainability of the program's implementation need to be evaluated comprehensively to give decision makers the sustainability of the program going forward. The evaluation uses the context, input, process, product (CIPP) model by analyzing the objectives, planning, implementation planning and the certification program results. The study was conducted at the Jakarta Librarian Professional Certification Institute (LSP) competency test site. Based on interview data, focus group discussions, observations, and study of related documents it is known that the program has been carried out by applicable procedures and regulations. So that in general, the Librarian LSP is eligible to provide a certificate of competence to the librarian following the results of the competency certification test package that is followed. However, there are still several aspects that need to be corrected and refined immediately, bearing in mind that the certification program has an impact on librarians for career development and increasing competitive value for their parent institutions. Optimizing the performance of Librarian LSPs or the formation of other forms of Librarian LSPs is needed to accelerate the certification of Indonesian librarians.